Knowledge and Practice Regarding Antenatal Care Among Pregnant Women Attending in a Government Hospital, Biratnagar - KC, Mamta; Rana, Muna; Shah, Bimala Kumari; KC, Nyamika; Bhattarai, Smita (Journal of Nobel Medical College, 2026)
Background: Antenatal care is one of the basic components of maternal care, on which the lives of mothers and babies depend. It is a key strategy to decrease maternal mortality in low-resource settings. The aim of the study was to assess knowledge and practice regarding antenatal care among pregnant women attending in a government hospital, Biratnagar.Materials and Methods: A descriptive cross-sectional research design was adopted to conduct this study. The study was carried out in Koshi zonal hospital, Biratnagar among 190 pregnant women attending antenatal out-patient department selected by non-probability convenient sampling technique. Data was collected by using structured interview schedule. Data were analyzed using descriptive statistics (frequency, percentage, mean and standard deviation) and inferential statistics (chi-square).Results: Finding revealed that majority (85.8%) and more than four-fifths (86.3%)  of the respondents had adequate level of knowledge and practice regarding antenatal care respectively. Significant association was seen between level of knowledge and different socio-demographic variables namely place of residence (p=0.048), religion (p=0.041), educational status of women (p=0.001) and economic status (p=0.02). Also, level of practice regarding antenatal care was significantly associated with educational status of women (p